PENYULUHAN DAN PENDAMPINGAN PENANGANAN SENGKETA TUMPANG TINDIH KLAIM LAHAN DI SURABAYA DAN SIDOARJO DENGAN PENDEKATAN PARTICIPATORY ACTION RESEARCH - Ansori, Lutfil; Bagus, Moh (As-Sidanah : Jurnal Pengabdian Masyarakat, 2026)
The problem of overlapping land claims is an agrarian issue that continues to arise in urban and peri-urban areas, including Surabaya and Sidoarjo, due to a mismatch between land conditions and residents' legal data. This activity focuses on counseling and legal assistance for communities facing unclear ownership status, incomplete documentation, and changes in land history resulting from regional development. This community service uses a Participatory Action Research (PAR) approach, involving residents as the main actors in identifying problems, mapping ownership histories, analyzing documents, and developing dispute-resolution steps. Through field observations, discussions, and focus groups, the activity resulted in a significant increase in community understanding of the differences between proof of ownership and proof of rights, land registration mechanisms, and the risks of transactions without a Land Deed Official (PPAT). Administrative assistance helps residents verify documents, resolve boundary conflicts through deliberation, and prepare certification files. The results of the activity indicate that implementing PAR can strengthen communities' social and legal capacity to handle land disputes more independently, collaboratively, and sustainably.